ARUS KOMUNIKASI KEPALA DESA DALAM PELAYANAN MASYARAKAT DESA KARYA INDAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Yana, Indri; Auza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The importance of communication with humans is the thing that cannot be denied by the man himself, so too does the organization. A problem that often occurs in an organization is less effective channelling of information in internal communication good communication up, down and horizontally. This is because in an organization, there is a dynamic process, in which human relations therein can be fickle and coordinated. In the Office of the village the beautiful work of Subdistrict of Kampar Regency head Tapung village held by the Camat Tapung. It was due because the village chief who served before involved an issue. One of the problems that arise a result of those policies is in charge of the village is not the Office of administrative management of the village, the village becomes slow, and service to the community is not the maximum. Some people complain over the administrative service in the village Works Beautifully because rarely meet with the village chief, only to hear a complaint over their fate.Research using qualitative descriptive method based on primary and secondary data sources and data collection using the techniques of observation, interview and documentation, with the determination of the informant through the sampling of saturated as many as six people that is the village chief, Secretary of the village and four people Kaur of village, as well as incidental sampling namely three communities, data analysis techniques using interactive data analysis models, Miles and Huberman by collecting data obtained are then processed for reduced, served so that generated a general conclusion.The results showed that the current downward communication is done by the method of spoken and written, although the most dominant is the oral communication through the medium of telephone and communications types and under the form dilakuka instructions/tasks, information and communication flows, revert to the top has the function of providing valuable information to the decision-maker i.e. the village head, while the horizontal communication is done in order to coordinate tasks and mutual information between many employees , and horizontal communication method used is through the meetings of the Committee, called the informasl at the time of rest and hours of phone conversations.Keywords: Flow Of Communication, Community Service